W obronie marketingu politycznego - Scheffs, Łukasz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The immediate cause of the article was the discussion launched by the editors of “Refleksje”. Its theme was the subject of knowledge in political science. The main reason for taking this issue was a book by Ryszard Skarzyński – The Basic Dilemma of Political Science: The Discipline of Science and Conventional Knowledge about Society. The Tradition of the University and the Demarcation of Knowledge. The main objective of the article is the reconstruction of views on political marketing and the politics. The article contains a review of the various theoretical positions on this subject. It is clear that political marketing is not just a “governance engineering” or “manipulation of people” but first and foremost a comprehensive set of the prospects for political parties, which only justifies the need to analyze this complex process.